Trade Progress Report : Doha Development Agenda and Aid for Trade. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Updates the Board on progress in the WTO negotiations under the Doha Development Agenda in the run-up to the Hong Kong SAR Ministerial in December, and presents proposals on aid for trade to be submitted to the Development Committee and International Monetary and Finance Committee in September as requested during the spring meetings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet